Analysis of Fluctuative Asimetry in Oreochromis niloticus (Linnaeus) in Mainit, Surigao Del Norte, Philiphines - Beltran, Darlo Novo M.; Magdugo, Rexie P. (Bionature, 2024)
This study analyzes fluctuating asymmetry (FA) in body shapes of pond-raised and wild type of Oreochromis niloticus to assess morphological variations. Using Procrustes ANOVA, significant differences were found in directional (p < 0.0001) and fluctuating asymmetry between populations. Principal Component Analysis (PCA) revealed that for male Tilapia, cumulative variation reached 74.15%, with PC1 contributing 29.04%. For females, the cumulative variation was 74.99%, with PC1 accounting for 24.97%. Key landmarks affected included the snout tip in males and several features in females, such as the dorsal fin insertion and eye margin. These landmarks indicate major morphological differences between the two populations. Geographic isolation, food availability, and environmental conditions likely contribute to the observed variations. The study highlights the effectiveness of fluctuating asymmetry analysis in characterizing body shape differences in Tilapia, emphasizing the need to consider environmental factors and stressors when interpreting these morphological variations, which may have implications for reproduction and development.